8(2-(3+6x))-4x=-10+2(1-26x)

Simple and best practice solution for 8(2-(3+6x))-4x=-10+2(1-26x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(2-(3+6x))-4x=-10+2(1-26x) equation:



8(2-(3+6x))-4x=-10+2(1-26x)
We move all terms to the left:
8(2-(3+6x))-4x-(-10+2(1-26x))=0
We add all the numbers together, and all the variables
8(2-(6x+3))-4x-(-10+2(-26x+1))=0
We add all the numbers together, and all the variables
-4x+8(2-(6x+3))-(-10+2(-26x+1))=0
We calculate terms in parentheses: -(-10+2(-26x+1)), so:
-10+2(-26x+1)
determiningTheFunctionDomain 2(-26x+1)-10
We multiply parentheses
-52x+2-10
We add all the numbers together, and all the variables
-52x-8
Back to the equation:
-(-52x-8)
We get rid of parentheses
-4x+8(2-(6x+3))+52x+8=0
We add all the numbers together, and all the variables
48x+8(2-(6x+3))+8=0
We move all terms containing x to the left, all other terms to the right
48x+8(2-(6x+3))=-8

See similar equations:

| 6x-3=-18x+x | | z+43=38 | | 3+8*m=3*2+-1 | | x2+5x−63=3x | | x​2​+5x−63=3x | | 7n-6=n+4 | | x​2​​+5x−63=3x | | x=134 | | 2(2b+1)=9(3b-6) | | 1.32=b/2-1.6 | | x^2-5x-70=-8x | | -24=-7n+3+8 | | p-22=-47 | | -(8z-(12z+8))=8+(3z+0) | | 27(q-938)=756 | | 3p+9p=3+p | | 8n-8n=5 | | -2/3/4=6/3/5b | | 3(12+4y)-5y=15 | | 25+13x=2x | | 14(p+30)=714 | | 1=n+20 | | 2/6x=5/8 | | 0=6w+13 | | -5(p+1)-p-6=-6(p+4)+13 | | 6x-4=5/2(3x-5) | | 9m-4(2m-3)=16 | | 10j+62=-718 | | 36+2x*x=81 | | -2(-4x+5)=54 | | 3x^2-9x-7=5 | | 2x/3=x/2=1/3 |

Equations solver categories